Flash Atomization: A New Concept to Control Combustion Instability in Water-Injected Gas Turbines. (21st February 2012) - Iyengar, Vishwas; Simmons, Harold; Ransom, David
Abstract : The objective of this work is to explore methods to reduce combustor rumble in a water-injected gas turbine. Attempts to use water injection as a means to reduce NOX emissions in gas turbines have been largely unsuccessful because of increased combustion instability levels. This pulsation causes chronic fretting, wear, and fatigue that damages combustor components. Of greater concern is that liberated fragments could cause extensive damage to the turbine section. Combustion instability can be tied to the insufficient atomization of injected water; large water droplets evaporate non-uniformly that lead to energy absorption in chaotic pulses. Added pulsation is amplified by the combustion process and acoustic resonance. Effervescent atomization, where gas bubbles are injected, is beneficial by producing finely atomized droplets; the gas bubbles burst as they exit the nozzles creating additional energy to disperse the liquid. A new concept for effervescent atomization dubbed "flash atomization" is presented where water is heated to just below its boiling point in the supply line so that some of it will flash to steam as it leaves the nozzle. An advantage of flash atomization is that available heat energy can be used rather than mechanical energy to compress injection gas for conventional effervescent atomization.